Evaluation of Physicochemical Parameters of Water in Three Lakes of Dindigul District, Tamil Nadu, India - Selvasubramani, Agalya; Marthandam, Priyadarshini Kasthuri; Manickam, Senguttuvan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The investigator's goal was to evaluate the effects of pesticide pollution brought on by the vegetable market's wastewater outflow from nearby ponds in and around Dindigul town, Tamilnadu, India. The surrounding research area's ponds have been greatly impacted by the ongoing use of pesticides in these vegetable wastes. Three sampling sites were chosen for this study such as Sadayan, Lakshmi Puram and Nagammal pondss and samples were taken in the summer to examine critical parameters like total hardness, pH, dissolved carbon dioxide (CO2), dissolved oxygen (DO), chemical oxygen demand (COD), biological oxygen demand (BOD), chloride, total alkalinity, and total dissolved solids (TDS), as well as heavy metals. The results indicate that Sadayan Ponds is classified as severely polluted while compared other ponds. This investigation leads to the conclusion that the ponds's water is not appropriate for agriculture or for sustaining wildlife.